Constructing The Bridge of Understanding: The Role of Habit of Mind, Resilience, and Mathematical Self-Confidence in Solving HOTS Problems - Sofitri, Devi Rinjani; Nugraheni, Nursiwi (Syntax Corporation, 2024)
This study aims to analyze the influence of Habit of Mind, Mathematical Resilience, and Self-Confidence on the ability of fifth-grade students at SDN Gugus Gajah Mungkur, Gajah Mungkur District, Semarang City, to solve HOTS mathematics problems. Employing a quantitative approach with a correlational design, the research sample consists of 110 students, selected through proportional random sampling from a population of 136 students across five elementary schools within the Gajah Mungkur cluster. The research instruments include a mathematical reasoning ability test and a questionnaire to measure the independent variables. Data collection techniques involve tests and questionnaires, while data analysis employs descriptive analysis using Microsoft Excel 2016 and inferential analysis using statistical software such as SPSS. This includes conducting correlation tests, and regression tests, after verifying analysis requirements like normality, linearity, homoscedasticity, and autocorrelation. The results reveal a positive and significant relationship between Habit of Mind, Mathematical Resilience, and Self-Confidence, and the students' ability to solve HOTS Mathematics problems. Thus, this study highlights the importance of developing these three psychological aspects to enhance high-level mathematical problem-solving skills. Consequently, Habit of Mind, Mathematical Resilience, and Self-Confidence significantly contribute to improving students' abilities in solving HOTS Mathematics problems.